Methicillin-Resistant Staphylococcus aureus Blood Isolates Harboring a Novel Pseudo-staphylococcal Cassette Chromosome mec Element - Yoon, Eun-Jeong; Lee, Hyukmin; Kim, Dokyun; Shin, Jong Hee; Shin, Jeong Hwan; Jeong, Seok Hoon (Frontiers in Microbiology, 2019)
The aim of this work was to assess a novel pseudo-staphylococcal cassette chromosome mec (SCCmec) element in methicillin-resistant Staphylococcus aureus (MRSA) blood isolates. Community-associated MRSA E16SA093 and healthcare-associated MRSA F17SA003 isolates were recovered from the blood specimens of patients with S. aureus bacteremia in 2016 and in 2017, respectively. Antimicrobial susceptibility was determined via the disk diffusion method, and SCCmec typing was conducted by multiplex polymerase chain reaction. Whole genome sequencing was carried out by single molecule real-time long-read sequencing. Both isolates belonged to sequence type 72 and agr-type I, and they were negative for Panton-Valentine leukocidin and toxic shock syndrome toxin. The spa-types of E16SA093 and F17SA003 were t324 and t2460, respectively. They had a SCCmec IV-like element devoid of the cassette chromosome recombinase (ccr) gene complex, designated as SCCmecE16SA093. The element was manufactured from SCCmec type IV and the deletion of the ccr gene complex and a 7.0-kb and 31.9-kb portion of each chromosome. The loss of the ccr gene complex results in the mecA gene becoming immobile in MRSA, which would be an adaptive evolutionary mechanism for survival in an antimicrobial-abundant environment. For this reason, the dissemination of this clone should be monitored closely.